2004
DOI: 10.1021/jp031349m
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and Disappearance of Dendritic and Chiral Patterns in Domains of Langmuir Monolayers Observed with Brewster Angle Microscopy

Abstract: Investigations on the aggregation behavior and morphology of Langmuir films of enantiomeric (L) and racemic (DL) N-acyl amino acids on pure aqueous as well as metal cation containing subphases were carried out at the mesoscale level with the help of Brewster angle microscopy (BAM). In the case of N-hexadecanoyl alanine on a pure aqueous subphase at 298 K the L-enantiomer forms crystal platelets, while the irregular fractal-like shape of the domains of the racemic mixture can be explained by a diffusion limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…6A and B. All NAAs (n = [11][12][13][14][15][16][17][18][19][20] gave several sharp diffraction peaks in the 2Â range of 1-20 • . From the position of these diffraction peaks the d-spacings were calculated; in each case 4-6 peaks were used to estimate the d-spacing and the average values obtained together with standard deviations are given in Table S7.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…6A and B. All NAAs (n = [11][12][13][14][15][16][17][18][19][20] gave several sharp diffraction peaks in the 2Â range of 1-20 • . From the position of these diffraction peaks the d-spacings were calculated; in each case 4-6 peaks were used to estimate the d-spacing and the average values obtained together with standard deviations are given in Table S7.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…Therefore, it is important to characterize them with respect to their structure and phase behavior and interaction with major membrane lipids such as phosphatidylcholines, phosphatidylethanolamines, and cholesterol. In previous work, it has been shown that N-palmitoyl alanine forms stable monolayers at the air-water interface where it exhibits chiral interactions that are temperature dependent and forms dendritic and chiral patterns as observed by Brewster angle microscopy [16,17]. In addition, some preliminary studies on the aggregation and calorimetric properties have been reported for a few NAAs [18,19].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…layers. L films of Ala [1][2][3], Asp [4], Ser [5][6], Val [3] etc. alkyl derivatives have been studied on different subphases.…”
Section: Introductionmentioning
confidence: 99%
“…Specific interactions can take place between similar enantiomers or between enantiomers of opposite sign. As a result, the chirality of AAS influences the physical properties of Langmuir monolayers, the films being formed either on an aqueous medium or on various surfaces [7][8][9][10][11][12][13][14][15][16][17][18]. It also determines molecular packing in the solid state, influencing the melting point, Krafft temperature and enthalpy of solution [19][20][21].…”
Section: Introductionmentioning
confidence: 99%